Changes experienced by physicians and nurses after a region-based palliative care intervention trial: the OPTIM-study - Suzuki, Satoshi; Eguchi, Kenji; Morita, Tatsuya; Miyashita, Mitsunori; Nozue, Yoshiko; Kinoshita, Hiroya; Hanada, Yoko; Shirahige, Yutaka (Palliative Care Research, 2012)
The primary aim of this study was to collect the views of physicians and nurses in the regions where community-based palliative care intervention trial, the OPTIM-study, was performed. A content analysis of free comments of the questionnaire survey was conducted. Questionnaires were mailed to 1,763 physicians and 3,156 nurses after the intervention, and 706 and 2,236 responses were obtained, respectively. A content analysis identified 327 free comments from physicians and 737 from nurses. As favorable effects, the categories [Multidisciplinary teams and community networks were established] [Home-based care is widespread] [Medical knowledge and skills are acquired just as those involved in palliative care] emerged. The main effects of the community palliative care program included the establishment of multidisciplinary teams and community networks, development of home-based care, and increasing knowledge, skills, and awareness about palliative care.